Prediction of Mental Health by Religious Orientation and the Mediating Role of Death Anxiety among Nurses in the Covid-19 Pandemic - Akram Farhadi; Hamed Javadian; Pouya Farokhnezhad Afshar (Shiraz University of Medical Sciences, 2022)
Background: The COVID-19 pandemic has been around for more than a year as a global problem, the nurses being among the first groups involved in treating epidemics. In addition to becoming infected and dying from the disease, nurses also suffer from death anxiety. This study aimed to predict mental health by religious orientation and the mediating role of death anxiety among nurses in the COVID-19 pandemic.Methods: The present descriptive-analytical and cross-sectional study was conducted on 208 nurses working in the Central Hospital for the Treatment of COVID-19 patients who enrolled in the census in the Persian Gulf Martyrs Hospital in Bushehr. Data collection tools were the General Health Questionnaire-28 (GHQ-28), the Templer's Death Anxiety Scale (DAS), and the Revised Religious Orientation Scale (ROS). Data were analyzed by SPSS v.22 software using the Pearson correlation test and multiple regression analysis (α=0.01).Results: According to the findings, death anxiety significantly and negatively affected mental health (P<0.001, β=-0.54). Intrinsic religious orientation led to a reduction in death anxiety (P=0.01, β=-0.16) and improved mental health (P<0.001, β=0.40), while extrinsic socially-oriented religiousness resulted in increased death anxiety (P<0.001, β=0.19) and decreased mental health (P<0.001, β=-0.20).Conclusion: More than half of the nurses had death anxiety in the COVID-19 epidemic, which decreased their mental health. This study revealed that the intrinsic religious orientation positively reduced death anxiety and promoted mental health.